Development of Visual Media Products for Children with Special Needs at the Denpasar Autism Center - Gde Bagus Andhika Wicaksana; Anak Agung Istri Manik Warmadewi; Putu Nugrahaeni Widiasavitri (Fakultas Teknik Universitas Warmadewa, 2021)
The Special Needs Child Development Group is an educational service center for children with autism located in the PLA (Autism Service Center) Denpasar City. In the learning process, children with autism have special characteristics and characteristics in observing and responding to something and tend to capture information or learn faster by using visualization. One of the interesting ways to improve children's storytelling skills is to provide picture books. Because picture books have a visualization effect that can stimulate the eyes to enjoy the picture and understand the text that explains the picture. There are several important problems regarding visual media which consist of the need for alternative visual media products to train children's sensory which is still limited to seeing sensory stimuli, media that can train other sensory types such as audio, taste, and touch, Adjustment of Visual Media Products to psychological growth and development are needed. autistic children and locality characteristics of the types of visual media objects that are used as teaching materials do not characterize the regional environment in Indonesia because some of the visual media come from abroad. Visual media products for learning media can be in the form of books and types of interactive games with the aim of providing cognitive and motoric impact, with content that will be adapted to the psychological condition of the child, of course, by highlighting elements of local characteristics in the object design to facilitate the learning process for children with autism. In developing visual media products that are intended as learning media for autistic children, the method used is ADDIE (Analysis, Design, Development, Implementation, and Evaluation) which is a learning model based on which each phase of the implementation process produces learning stages designed with specific objectives The sustainability aspect of this PKM program is the development of advanced visual media products and the design of special facilities for autistic children. So that gradually the needs and access to better education can be obtained by all children with special needs on a city and regional scale.